MENAIKKAN GENGSI PRODUK UKM BERBAHAN BAKU DAUN KELOR MELALUI REBRANDING DAN PEMASARAN ONLINE - Mustika Winedar; Nur Sayidah; Alvy Mulyaning Tyas (Jurnal Abdi Masyarakat Multidisiplin, 2022)
This community service program partners with SMEs producing Moringa leaf powder capsules who have problems with low sales levels and limited marketing reach. This community service activity aims to increase sales of Moringa leaf powder capsule products through rebranding strategies and the use of online marketing media. The rebranding strategy allows the product to be better known to the public from the name that the product bears. Meanwhile, product marketing through online media has several advantages, including unlimited marketing area coverage and low cost. The implementation of this community service activity is carried out using the Focus Group Discuss method in order to finalize the rebranding plan and online marketing strategy, which is followed by the mentoring method. The results of this activity were the creation of a new Moringga brand, new packaging designs, social media accounts as online marketing tools, obtaining P-IRT permits and distribution permits for herbal supplements from BPOM. By looking at the available market share which is still quite wide, and the availability of abundant raw materials, the implementation of rebranding strategies and online marketing can increase sales of Moringa leaf powder in capsule form, thereby increasing partner income. Keywords : Moringa, Branding, Marketing, Online